The occurrence of antimicrobial resistance and class 1 integrons among commensal Escherichia coli isolates from infants and elderly persons - Kõljalg Siiri; Truusalu Kai; Lõivukene Krista; Stsepetova Jelena; Sepp Epp; Naaber Paul; Mikelsaar Marika (BMC, 2009)
Abstract Background The aim of our study was to compare the presence of the intI1 gene and its associations with the antibiotic resistance of commensal Escherichia coli strains in children with/without previous antibiotic treatments and elderly hospitalized/healthy individuals. Methods One-hundred-and-fifteen intestinal E. coli strains were analyzed: 30 strains from 10 antibiotic-naive infants; 27 from 9 antibiotic-treated outpatient infants; 30 from 9 healthy elderly volunteers; and 28 from 9 hospitalized elderly patients. The MIC values of ampicillin, cefuroxime, cefotaxime, gentamicin, ciprofloxacin, and sulfamethoxazole were measured by E-test and IntI1 was detected by PCR. Results Out of the 115 strains, 56 (49%) carried class 1 integron genes. Comparing persons without medical interventions, we found in antibiotic-naive children a significantly higher frequency of integron-bearing strains and MIC values than in healthy elderly persons (53% versus 17%; p < 0.01). Evaluating medical interventions, we found a higher resistance and frequency of integrons in strains from hospitalized elderly persons compared with non-hospitalized ones. Children treated with antibiotics had strains with higher MIC values (when compared with antibiotic-naive ones), but the integron-bearing in strains was similar. In most cases, the differences in resistance between the groups (integron-positive and negative strains separately) were higher than the differences between integron-positive and negative strains within the groups. Conclusion The prevalence of integrons in commensal E. coli strains in persons without previous medical intervention depended on age. The resistance of integron-carrying and non-carrying strains is more dependent on influencing factors (hospitalization and antibiotic administration) in particular groups than merely the presence or absence of integrons.